Self-DNA driven inflammation in COVID-19 and after mRNA-based vaccination: lessons for non-COVID-19 pathologies - Heil, Martin (Frontiers in Immunology, 2024)
The coronavirus disease 2019 (COVID-19) pandemic triggered an unprecedented concentration of economic and research efforts to generate knowledge at unequalled speed on deregulated interferon type I signalling and nuclear factor kappa light chain enhancer in B-cells (NF-κB)-driven interleukin (IL)-1β, IL-6, IL-18 secretion causing cytokine storms. The translation of the knowledge on how the resulting systemic inflammation can lead to life-threatening complications into novel treatments and vaccine technologies is underway. Nevertheless, previously existing knowledge on the role of cytoplasmatic or circulating self-DNA as a pro-inflammatory damage-associated molecular pattern (DAMP) was largely ignored. Pathologies reported ‘de novo’ for patients infected with Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV)-2 to be outcomes of self-DNA-driven inflammation in fact had been linked earlier to self-DNA in different contexts, e.g., the infection with Human Immunodeficiency Virus (HIV)-1, sterile inflammation, and autoimmune diseases. I highlight particularly how synergies with other DAMPs can render immunogenic properties to normally non-immunogenic extracellular self-DNA, and I discuss the shared features of the gp41 unit of the HIV-1 envelope protein and the SARS-CoV 2 Spike protein that enable HIV-1 and SARS-CoV-2 to interact with cell or nuclear membranes, trigger syncytia formation, inflict damage to their host’s DNA, and trigger inflammation – likely for their own benefit. These similarities motivate speculations that similar mechanisms to those driven by gp41 can explain how inflammatory self-DNA contributes to some of most frequent adverse events after vaccination with the BNT162b2 mRNA (Pfizer/BioNTech) or the mRNA-1273 (Moderna) vaccine, i.e., myocarditis, herpes zoster, rheumatoid arthritis, autoimmune nephritis or hepatitis, new-onset systemic lupus erythematosus, and flare-ups of psoriasis or lupus. The hope is to motivate a wider application of the lessons learned from the experiences with COVID-19 and the new mRNA vaccines to combat future non-COVID-19 diseases.